2021
DOI: 10.1038/s41598-021-94466-0
|View full text |Cite
|
Sign up to set email alerts
|

Yoga versus massage in the treatment of aromatase inhibitor-associated knee joint pain in breast cancer survivors: a randomized controlled trial

Abstract: Aromatase inhibitors (AIs) are standard adjuvant therapy for postmenopausal women with oestrogen receptor-positive, early-stage, and metastatic breast cancer. Although effective, the risk of falls due to AI-associated knee joint pain significantly increased. The aim of this study was to evaluate the therapeutic effects of yoga and massage on AI-associated knee joint pain. Breast cancer survivors were randomly assigned to a 6-week yoga intervention-2-week rest-6-week massage exposure (Yoga first, n = 30) or a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Although acupoint stimulation still needs to be incorporated into the cancer palliative care system, we cannot ignore the palliative effect of acupoint stimulation on cancer. For instance, acupoint stimulation is useful not only to reduce the side effects of chemotherapy but also to relieve tumor-related symptoms (including fatigue, insomnia, and cancer pain) and relieve tumor treatment-related side effects [including constipation caused by opioid peptides ( 72 ), lymphedema after breast cancer surgery ( 73 ), and knee pain caused by aromatherapy enzyme inhibitors ( 74 , 75 )]. Taking cancer pain as an example, acupoint stimulation is beneficial for patients with moderate to severe cancer pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although acupoint stimulation still needs to be incorporated into the cancer palliative care system, we cannot ignore the palliative effect of acupoint stimulation on cancer. For instance, acupoint stimulation is useful not only to reduce the side effects of chemotherapy but also to relieve tumor-related symptoms (including fatigue, insomnia, and cancer pain) and relieve tumor treatment-related side effects [including constipation caused by opioid peptides ( 72 ), lymphedema after breast cancer surgery ( 73 ), and knee pain caused by aromatherapy enzyme inhibitors ( 74 , 75 )]. Taking cancer pain as an example, acupoint stimulation is beneficial for patients with moderate to severe cancer pain.…”
Section: Discussionmentioning
confidence: 99%
“…We performed subgroup analyses on exercise type for stretching exercise, aerobic exercise (plus stretching exercise), resistance training (plus stretching exercise), and a combination of aerobic exercise and resistance training (plus stretching exercise). The subgroup analysis for stretching exercise (2 studies; n=88) included yoga (39,40) and did not show a significant effect on pain (SMD −0.80; 95% CI: −1.87 to 0.27; P=0.14; Figure 7A). Subgroup analysis for aerobic exercise (plus stretching exercise) involved waterbased physical exercise, core stabilization with aerobic exercise, Nordic walking, web-and mobile-based lymphatic exercise, and home-based walking exercise (5 studies; n=312) (41)(42)(43)(44)(45), and demonstrated a significant effect on pain (SMD −0.55; 95% CI: −1.02 to −0.07; P=0.02; Figure 7A).…”
Section: Effect Of Physical Exercise On Painmentioning
confidence: 99%
“…The efficacy of physical exercise on pain was investigated in 13 RCTs (n=761) (39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51). Treatments included a variety of exercise types, durations, and frequencies.…”
Section: Effect Of Physical Exercise On Painmentioning
confidence: 99%
See 2 more Smart Citations